Measurement of the mass of the top quark in decays with a J/psi meson in pp collisions 8 Tev - (:unkn) unknown (SPRINGER, 2016)
A first measurement of the top quark mass in the decay channel t -> (W -> l nu)(b -> J/psi + X -> mu(+) + mu(-) + X) is presented. The analysis uses events selected from the proton-proton collisions recorded by the CMS detector at the LHC at a center-of-mass energy of 8TeV. The data correspond to an integrated luminosity of 19.7 fb(-1), with 666 t (t) over bar and single top quark candidate events containing a reconstructed J/psi candidate decaying into an oppositely-charged muon pair. The mass of the (J/psi + l) system, where l is an electron or a muon from W boson decay, is used to extract a top quark mass of 173.5 +/- 3.0 (stat) +/- 0.9 (syst) GeV.
Keywords: Hadron-Hadron scattering (experiments); Top physics; LHC